2008
DOI: 10.1128/aac.00375-07
|View full text |Cite
|
Sign up to set email alerts
|

Replication of Colonic Crohn's Disease Mucosal Escherichia coli Isolates within Macrophages and Their Susceptibility to Antibiotics

Abstract: There is increasing evidence that Escherichia coli organisms are important in Crohn's disease (CD) pathogenesis. In CD tissue they are found within macrophages, and the adherent-invasive CD ileal E. coli isolate LF82 can replicate inside macrophage phagolysosomes. This study investigates replication and antibiotic susceptibility of CD colonic E. coli isolates inside macrophages. Replication of CD colonic E. coli within J774-A1 murine macrophages and human monocyte-derived macrophages (HMDM) was assessed by cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
99
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(103 citation statements)
references
References 70 publications
4
99
0
Order By: Relevance
“…A few CD-associated microbial species have been described (notably AIEC and Mycobacterium species) that appear able to either bypass an intact intestinal barrier or evade or suppress macrophage function [24,[67][68][69]. These species might therefore be able to initiate a chronic inflammatory response even in 'innate immunocompetent' hosts.…”
Section: Europe Pmc Funders Author Manuscriptsmentioning
confidence: 99%
See 1 more Smart Citation
“…A few CD-associated microbial species have been described (notably AIEC and Mycobacterium species) that appear able to either bypass an intact intestinal barrier or evade or suppress macrophage function [24,[67][68][69]. These species might therefore be able to initiate a chronic inflammatory response even in 'innate immunocompetent' hosts.…”
Section: Europe Pmc Funders Author Manuscriptsmentioning
confidence: 99%
“…Although it is impossible to establish causality with this approach, focused metagenomic studies represent a powerful tool for further study of this aspect of the intestinal environment in health and disease and should be applied across populations. Bifidobacterium species and Faecalibacterium prausnitzii appear to have a clinically relevant association with CD, but it remains to be determined whether 'restoration' or alteration of the balance of microbial species in the bowel is of therapeutic benefit [65,66] (although again, this would not necessarily demonstrate causality).A few CD-associated microbial species have been described (notably AIEC and Mycobacterium species) that appear able to either bypass an intact intestinal barrier or evade or suppress macrophage function [24,[67][68][69]. These species might therefore be able to initiate a chronic inflammatory response even in 'innate immunocompetent' hosts.…”
mentioning
confidence: 99%
“…Antimicrobial treatments were colicin E1, colicin E9, and colicin E9-H575A, a variant protein that lacks antibacterial activity because of a mutation in the active site of the cytotoxic DNase domain, or ciprofloxacin, which has previously been shown to be highly active against intramacrophagic AIEC. 45 For antibiotic-free controls, the number of bacteria present in RAW264.7 macrophages at 4 hours and 24 hours was approximately 1.6 · 10 4 and 800 CFUs per well, respectively (see Fig., Supplemental Digital Content 2, http://links.lww.com/IBD/A972). Both colicin E9-and colicin E1-treated macrophages showed reduced intracellular survival of LF82 within macrophages at both 4 and 24 hours, but to a lesser extent than ciprofloxacin (Fig.…”
Section: Macrophagesmentioning
confidence: 99%
“…Studies in our laboratory concluded that azithromycin, ciprofloxacin, rifampicin, sulfamethoxazole, tetracycline and trimethoprim were all effective against E. coli within macrophages. 56 Use of single antibiotics is likely to be unsuccessful in Crohn's disease because of the development of bacterial resistance. Thus a controlled trial showed that clarithromycin as a single agent was apparently effective for one month but then lost efficacy by the principal endpoint at 3 months.…”
Section: Efficacy Of Antibioticsmentioning
confidence: 99%
“…16,56 They can be seen within double membrane vesicles, implying that they are able to survive within autophagosomes. Further research is needed to understand how they evade killing by the macrophages.…”
mentioning
confidence: 99%